Video Feature Making in ESP- Based Public Speaking Class: A Student-Centred Learning in Vocational Higher Education Context - Apriyanti, Difiani -; Syarif, Hermawati; Ramadhan, Syahrul (International Journal of Language Education, 2021)
In Indonesia, English for Specific Purpose usually offers to students of non-English Department. Actually, it must also be taught to students of English Department, especially who are in vocational higher institutions. By facilitating the learning of English for Specific Purpose by the institution, they will fit in any kinds of work fields later on. Actually, the process of learning English for Specific Purpose could be integrated in various subjects in English Department if the class is using the right learning material, like Digital Video Feature Project. It is a project assignment for Public Speaking class which is developed to improve students’ English for Specific Purpose by applying Gall and Borg Small Scale Model. The steps are need analysis, planning objectives, developing preliminary forms of product, preliminary field testing, and main field testing. This article is only discussing the last phase, which is analysing the effect of Digital Video Feature Project on the student’ English for Specific Purpose. The sample taken was a female English Department student of Politeknik Negeri Padang.  She enrolled in Public Speaking class, and chose English for Environmental Engineering for her English for Specific Purpose. She made a video feature about Waste Bank Program which is established by Padang Environmental Services Department. From the analysis  on the student’ self assessment form, the results are  the student is more competence writing in the context of Environmental Engineering,  is more skillfull as a public speaker in a topic related to Environmental Engineering field, her  knowledge related to Environmental Engineering  increases, and her social life with people related to Environmental Engineering is also built. In conclusion, video feature project of Waste Bank Program does not only influence the student’s ESP and public speaking skill, but also effect their mind and consideration to support the program.